Role of Micronutrients (Vitamins & Minerals) - Labia Arif; Muhammad Hamza; Esha Iqbal; Zain Kaleem (International Journal of Multidisciplinary Sciences and Arts, 2024)
Micronutrients are essential nutrients. Micronutrients are needed mostly below 100 milligrams per day for human nutrition, although macronutrients are needed in grams daily. Essential nutrients cannot be produced in human beings and, therefore needed by the diet. Micronutrients play a fundamental role in digestion and tissue maintenance but effects in inhibiting or medication of sickness which is not caused by lack of nutrients cannot be predictable from increasing the consumption. Medical insufficiency of nutrients is unfamiliar in industrialized nations i.e. High consumption of micronutrients such as folic acid and b-carotene is linked with a high threat of long-term illnesses for example cardiovascular disease, and inferior threat of congenital heart disease and cancer at different places. Above 2 billion persons in both developing and industrial Countries are disturbed by deficiencies. The actions or absorption of vitamins is slowed down by Anti-vitamins i.e., enzymes that use vitamin B1 are suppressed by Pyrithiamine. Biotin absorption is inhibited by avidin, although by cooking it is inactivated. In the human body four main basic elements (O, H, C, and N) by weight, are often not involved in the tilts of main minerals. For plants, nitrogen is a “mineral" because it is normally involved in manures. 96% of the weight of the human body is composed of these elements, and the remaining percent is composed of trace elements and macrominerals. Phosphorus, Calcium, sodium, potassium, and magnesium (macro minerals, microelements) are the five main elements in the human body. Sulfur, manganese, molybdenum, copper, iodine, selenium zinc, chlorine, cobalt, and iron are microelements, with specific biological functions in the human body. The current review analyzes the different methodologies for the study of nutritive consumption of micronutrients and will reflect the indication of the valuable influence of the supplements of micronutrients on health.